Herbert Ernst Wiegand: Internationale Bibliographie zur germanistischen Lexikographie und Wörterbuchforschung - Smit, Maria (Lexikos, 2007)
These are the first two volumes of a three-part international bibliography of German lexicography and dictionary research. The third part will appear in two separate volumes in the near future. This review therefore does not deal with the entire publication, but mainly highlights Wiegand’s approach to the compilation of this bibliography, discussing several aspects of the items he included.